Clinical Profile, Predictors of Mortality, and Treatment of Patients after Myocardial Infarction, in an Academic Medical Center Hospital - Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Assalin, Vanessa M. [UNESP]; Pola, Patrícia M. S. [UNESP]; Becker, Luís E. [UNESP]; Okoshi, Marina Politi [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Inoue, Roberto M. T. [UNESP]; Spadaro, Joel [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2002)
OBJECTIVE: To evaluate clinical profiles, predictors of 30-day mortality, and the adherence to international recommendations for the treatment of myocardial infarction in an academic medical center hospital. METHODS: We retrospectively studied 172 patients with acute myocardial infarction, admitted in the intensive care unit from January 1992 to December 1997. RESULTS: Most patients were male (68%), white (97%), and over 60 years old (59%). The main risk factor for coronary atherosclerotic disease was systemic blood hypertension (63%). Among all the variables studied, reperfusion therapy, smoking, hypertension, cardiogenic shock, and age were the predictors of 30-day mortality. Most commonly used medications were: acetylsalicylic acid (71%), nitrates (61%), diuretics (51%), angiotensin-converting enzyme inhibitors (46%), thrombolytic therapy (39%), and beta-blockers (35%). CONCLUSION: The absence of reperfusion therapy, smoking status, hypertension, cardiogenic shock, and advanced age are predictors of 30-day mortality in patients with acute myocardial infarction. In addition, some medications that are undoubtedly beneficial have been under-used after acute myocardial infarction.
Keywords: myocardial infarction; mortality; treatment